Mindfulness-Based Therapy and Neural Reconfiguration - Galvez-Contreras, Alma; Gonzalez-Castañeda, Rocio; Gonzalez-Perez, Oscar (Achievements and Challenges of Medicine and Medical Science Vol. 5, 2024)
Mindfulness was initially translated from the Indian term "Sati," which denotes awareness, attention, and memory. Mindfulness-Based Programs (MBP), particularly Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT), highlight their efficacy in managing stress and preventing relapse in mental health disorders. These programs are recognized as third-generation therapies within Cognitive-Behavioral Therapy, emphasizing acceptance of internal experiences. This chapter examined neuroimaging studies that reveal mindfulness-induced neural changes in brain regions associated with cognitive control and emotional regulation, such as the prefrontal cortex and amygdala. Despite accessibility and holistic health improvements, the effectiveness of MBP can vary based on individual differences and practitioner expertise. Future research is needed to explore personalized mindfulness interventions and the integration of MBP with other therapeutic modalities to optimize outcomes and broaden accessibility.